(untitled) (Sahel Journal of Life Sciences FUDMA, 2025)
This study assessed the impact of thermal and high-pressure processing (HPP) on the proximate composition of Trichosanthes lobata. Fruits were collected from Kujama, Chikun LGA, Kaduna State, and authenticated at the Herbarium of the Botany Department, Ahmadu Bello University, Zaria. Proximate composition was determined using AOAC (2005) methods. Thermal processing at 80°C, 90°C, and 100°C significantly (P≤0.05) reduced moisture content, with samples at 90°C and 100°C showing no significant difference but lower values than 80°C. Crude protein declined across all thermally treated groups, lowest at 100°C. Fat and ash contents decreased insignificantly, while crude fiber reduced significantly. Carbohydrate content increased at 80°C and 90°C but declined slightly at 100°C, though not significantly different from the control. HPP at 250, 300, and 350 MPa also reduced moisture significantly, with 300 MPa yielding the highest reduction. Protein content remained unchanged at 250 MPa, declined slightly at 300 MPa, and increased at 350 MPa, though variations were not significant. Fat increased slightly at 250 and 300 MPa but decreased at 350 MPa. Ash declined insignificantly across HPP groups, while crude fiber reduced significantly. Carbohydrate content showed a notable increase under HPP. Overall, thermal processing caused greater nutrient losses, particularly in protein and fiber, whereas HPP preserved protein integrity and enhanced carbohydrates. The study highlights the comparative advantages of HPP over thermal methods in retaining the nutritional quality of T. lobata, offering useful insights for optimizing processing techniques.